Field study of experimental antifouling paint formulations (2011)
This work presents the results of field testing of several experimental antifouling paints, which were exposed for up to 471 days to natural sea water in the Caribbean. The testing site was selected in order to obtain very critical conditions; therefore, static panels were immersed in water considered as having an intense biological activity. Paints formulations are based in natural rosin as binder, and cuprous oxide as biocide. Three different plasticizers and binder/plasticizers ratios were employed, obtaining 22 different formulations, which were classified in three different groups according to their biocide leaching rate. Besides this, three commercial products were tested for comparison. Some of the experimental formulations, including paints with low biocide release rate, show as good or better performance than the commercial ones. From the plasticizers employed (chlorinated rubber, vegetable oleic acid, and vegetable oil), it was found that the best results were obtained with formulations prepared with chlorinated rubber. It was also observed that physical chemical water properties might have an important effect on paint efficiency, particularly the presence of particulate matter in the water or important variations of water oxygen content.